Method for determining, preventing and treating adhesion of iron-containing raw material in molten drop experiment
By identifying, preventing, and addressing adhesion issues in molten droplet experiments, we can ensure smooth experiment execution, reduce adhesion risks, decrease costs, improve accuracy, and provide support for blast furnace operations.
Patent Information
- Application Number
- CN202411383650.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
In the molten droplet experiment of iron-containing raw materials, the adhesion problem leads to experimental failure, raw material loss, increased costs and misjudgment of blast furnace conditions. Existing technologies are difficult to effectively identify, prevent and deal with the adhesion phenomenon.
The bonding condition is identified by the judgment method, the prevention method is to check the experimental equipment and design and improve the graphite pressure bar structure, and the treatment method includes physical removal and high temperature treatment of the bonded material.
It reduces the risk of droplet adhesion in molten droplet experiments, ensures smooth experiment execution, reduces material costs, improves experimental accuracy, and provides accurate data for blast furnace condition assessment.
Smart Images

Figure CN119290948A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of iron ore experiments, in particular to a method for determining, preventing and treating adhesion in a droplet experiment of an iron-containing raw material. Background Art
[0002] In the steel industry, blast furnace smelting raw materials mainly enter the blast furnace in the form of sintered ore, pelletized ore, lump ore, etc. As the blast furnace temperature rises, the raw materials enter the furnace and undergo a series of physical and chemical reactions such as thermal expansion, softening, melting, and dripping during the descent process. The softening start temperature T of the iron-containing raw material is measured by the soft melting dripping experiment. 10 , softening end temperature T 40 , Melting start temperature T s , dripping temperature T d , the maximum pressure difference and other parameters during the experiment simulate the soft melting, dripping, slag iron droplet flow and other properties of the raw materials entering the blast furnace, which is of great significance for characterizing the permeability of the blast furnace soft melting zone and the performance of the raw materials entering the furnace.
[0003] In the soft melting dripping experiment of iron-containing raw materials, the bonding problem has always been a major problem that hinders the experimental progress and troubles researchers. There are two main reasons for the accumulation of adhesives during the molten drop experiment: First, after the experimental raw materials melt and begin to drip, the liquid experimental raw materials drip from the leaking point of the bottom ring of the graphite crucible, and flow through the graphite pressure rod to the bottom graphite crucible. During the dripping process, the liquid experimental raw materials will adhere to the side wall of the graphite pressure rod. When the number of experiments is too many, the residual adhesives accumulate to a certain extent, and the adhesives will accumulate and hinder dripping, resulting in the adhesion and blockage of the graphite pressure rod. Second, during the soft melting dripping process of the experiment, when the liquid experimental raw materials pass through the intersection of the outer ring and the inner ring, they are easy to accumulate because of the insufficient slope at the bottom, resulting in a large amount of dripping at the interface between the outer ring and the inner ring of the graphite pressure rod at one time. In addition, there are residues on the side wall of the lower long section of the graphite pressure rod, which causes the dripping to accumulate and cause adhesion, hindering the forward flow of dripping, resulting in the adhesion and blockage of the graphite pressure rod.
[0004] When the droplet experiment has a sticking problem, it means that the droplet experiment has failed and the experimental raw materials used are scrapped. In addition to causing a certain amount of raw material loss, the loss of experimental raw materials that are in short supply for some scientific research projects may directly lead to project delays. Secondly, the graphite crucible sticking will increase the experimental cost, and the sticking of residues may cause the graphite pressure rod to be unable to be used normally, or even scratch the experimental furnace body and damage the internal corundum tube. Finally, if other factors cannot be eliminated when the droplet experiment sticks, the metallurgical properties of the experimental raw materials may be misjudged, which in turn affects the operator's judgment of the blast furnace condition. Therefore, in the soft melting dripping experiment of iron-containing raw materials, the determination, prevention and treatment methods of sticking are crucial. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for determining adhesion in a molten droplet experiment of an iron-containing raw material; the present invention also provides a method for preventing adhesion in a molten droplet experiment of an iron-containing raw material; the present invention also provides a method for treating adhesion in a molten droplet experiment of an iron-containing raw material.
[0006] In order to solve the above technical problems, the technical solution adopted by the determination method of the present invention is: when the following situation occurs during the molten drop experiment, it is determined that bonding occurs in the molten drop experiment: after the iron-containing raw material begins to melt, the pressure difference rises sharply to a peak, and then the pressure difference falls back and then rises again, forming a continuous curve of continuous decline and rise, and finally the pressure difference continues to increase and no longer decreases.
[0007] Furthermore, when bonding occurs in the molten drop test, no more dripping occurs or the dripping weight is ≤10g.
[0008] Furthermore, the lowest point of each pressure drop is located in the height range P h1 or P h2 Inner; said 1KPa<P h1 ≤P max , 0≤P h2 <1KPa.
[0009] In order to solve the above technical problems, the technical solution adopted by the prevention method of the present invention includes the following steps: 1) using a conical rod to check whether there is any adhesive residue left in the previous experiment in the lower pressure rod; 2) Check whether the holes at the bottom of the graphite indenter are smooth and not blocked by adhesives, whether the bottom of the indenter is flat and has no bumps, and whether the bottom surface is in stable contact with the test material; 3) Check whether the holes at the bottom of the graphite crucible are smooth and not blocked by adhesives, and whether there are any defects on the inner and outer walls of the graphite crucible.
[0010] Furthermore, the following graphite pressure rod is used: the diameter difference between the upper outer ring (1) and the lower inner ring (2) of the graphite pressure rod is 1 to 4 cm, and the bottom end slope of the upper outer ring (1) is 72.9° to 85.6°.
[0011] In order to solve the above technical problems, the technical solution adopted by the treatment method of the present invention includes the following processes: 1) when the adhesive is accumulated on the upper end of the lower long section of the graphite pressure rod, the bonding part of the graphite pressure rod is subjected to high temperature treatment to melt and discharge the adhesive residue; 2) When the adhesive accumulates at the end of the lower long section of the graphite pressure rod, use a tapered rod to physically remove the adhesive.
[0012] The beneficial effect of adopting the above technical scheme is that: based on the position and state of the droplet test adhesion, the present invention proposes two situations of the droplet test adhesion judgment, makes targeted prevention and treatment methods, reduces the risk of droplet test adhesion, and improves the experimental accuracy. The present invention reduces the adhesion risk of the droplet test, ensures the smooth progress of the droplet test, reduces the cost of experimental consumables, and ensures the accuracy of the droplet test by judging, preventing and treating the adhesion problem in the soft melt droplet test, thereby providing data support for the accurate judgment of the blast furnace condition.
[0013] The present invention proposes preventive measures for adhesion in molten drop experiment, including checking the residue of experimental equipment, checking the upper pressure head of experimental equipment, and checking the graphite crucible of experimental equipment, effectively preventing non-experimental factors from causing adhesion in molten drop experiment, and ensuring the smooth progress of molten drop experiment. Based on the position and state of adhesion in molten drop experiment, the present invention proposes two methods of physical treatment and high temperature treatment of adhesives, and further designs a new type of graphite pressure rod in combination with experimental equipment, which is conducive to reducing the adhesion residue rate of soft molten drop of raw materials during molten drop experiment, ensuring the smooth dripping of raw materials, ensuring the smooth progress of molten drop experiment, reducing experimental costs, and providing support for the stable and smooth operation of blast furnace; it has the characteristics of strong operability, simple process, and easy implementation. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0015] Figure 1 It is a schematic diagram of one of the determination situations of the present invention; Figure 2 It is a schematic diagram of another determination situation of the present invention; Figure 3 It is a front view structural diagram of the graphite pressure rod of the present invention; Figure 4 It is a top view of the structure of the graphite pressure rod of the present invention.
[0016] In the figure: upper outer ring 1; lower inner ring 2; bottom inner ring 3; bottom slope E. DETAILED DESCRIPTION
[0017] In the droplet experiment, 500±0.1g of experimental raw materials with a particle size of 10-12.5mm were screened. During the charging process, 80±0.1g of coke with a particle size of 10-12.5mm was laid on the bottom of the graphite crucible. After flattening, the experimental raw materials were placed in it and then 40±0.1g of coke with a particle size of 10-12.5mm was laid again. The experimental raw materials refer to the finished raw materials entering the furnace, including sintered ore, pelletized ore, lump ore, etc.
[0018] The method for preventing adhesion in the molten drop experiment of iron-containing raw materials is as follows: before the molten drop experiment begins, check the experimental equipment and whether there are any adhesives left after the last experiment. 1) Use a tapered rod to check whether there are any adhesives left in the lower pressure rod from the last experiment, especially the side wall of the port and the cylindrical tube part of the lower pressure rod, to prevent the accumulation of adhesives during the molten drop experiment and cause experimental adhesion. 2) Check whether the hole at the bottom of the upper pressure head is smooth and not blocked by adhesives, whether the bottom of the pressure head is flat and has no bumps, and whether the bottom surface is in stable contact with the experimental raw materials, to prevent the experimental raw materials from splashing out due to high-temperature liquefaction during the molten drop experiment and forming adhesives in the corundum tube of the furnace body. 3) Check whether the hole at the bottom of the graphite crucible is smooth and not blocked by adhesives, and whether the inner and outer walls of the graphite crucible, especially the ring wall at the top of the graphite crucible, are defective. 4) Design a new type of graphite pressure rod. According to the experience of previous droplet bonding experiments, the location of the adhesive accumulation is mainly concentrated in the inner ring section of the graphite pressure rod, which is divided into the position close to the outer ring at the top of the inner ring section and the position close to the tail end at the bottom of the inner ring section. Based on the main factors of droplet bonding experiments, the new graphite pressure rod is modified as follows: Figure 3 , Figure 4 As shown, the graphite pressure rod includes an upper outer ring 1, a lower inner ring 2 and a bottom inner ring 3; by reducing the diameter difference D between the upper outer ring 1 and the lower inner ring 2 of the graphite pressure rod, the bottom slope E of the connection between the upper outer ring 1 and the lower inner ring 2 of the graphite pressure rod is increased, so that the liquid experimental raw materials can pass through the connection between the upper outer ring 1 and the lower inner ring 2 of the graphite pressure rod faster during the soft melting dripping process, reduce the possibility of blockage, and reduce the risk of adhesion at the top of the long section of the lower inner ring 2 close to the position of the upper outer ring 1. The diameter difference D between the upper outer ring 1 and the lower inner ring 2 of the graphite pressure rod of the experimental equipment is the difference between the diameter D1 of the upper cylinder of the graphite pressure rod and the diameter D2 of the lower long section of the graphite pressure rod. A truncated cone with a wide top and a narrow bottom is formed at the connection between the upper outer ring 1 and the lower inner ring 2 of the graphite pressure rod, and the diameter difference D is reduced from the conventional 4 to 5 cm to 1 to 4 cm. The bottom slope E at the connection between the upper outer ring and the lower inner ring 2 of the graphite pressure rod is the angle formed by the upper outer ring 1 and the lower inner ring 2 of the graphite pressure rod. The bottom slope E increases from the conventional 68.9° to 72.9° to 72.9° to 85.6°.
[0019] This iron-containing raw material droplet test bonding determination method: Figure 1 , Figure 2 As shown in Figure 2, during the droplet experiment, the temperature gradually increased to the melting start temperature T s After that, the pressure difference in the furnace rises sharply until it reaches the peak, and the maximum pressure difference is recorded as P max After passing the apex, the pressure difference begins to gradually decrease, falling to the altitude range P h1 or P h2 The pressure difference inside the chamber rises again, and the pressure difference when it rises is recorded as P1, that is, the lowest point of the pressure difference reduction is P1. h1 ≤Pmax , 0≤P h2 <1KPa; the pressure difference rises for a short period and then drops again, and the falling pressure difference is recorded as P2. Then the pressure difference shows a continuous curve of continuous rise and fall, and the turning points are recorded as P3, P4, etc. until the last time the pressure difference rises and no longer decreases, and the last pressure difference rising point is recorded as P n ; said P1, P2, P3, P4...P n All within the height range P h1 or P h2 After that, the pressure difference value keeps increasing within the safe pressure range of the molten drop test, which can be judged as bonding in the molten drop test. At this time, no more dripping or the dripping weight is ≤10g. After it is judged that bonding occurs, in order to prevent further damage to the experimental equipment, it is necessary to manually close the molten drop test software on the computer, wait for the experimental equipment to cool down, and then take out the graphite crucible to treat the bonding area.
[0020] If adhesion occurs in the droplet test, solutions should be proposed for different adhesion situations, and the degree of adhesion should be determined by the location of the accumulation of adhesion residues. The adhesion treatment method for the iron-containing raw material droplet test is as follows: 1) When the adhesive is accumulated at the end of the lower long section of the graphite pressure rod, that is, the adhesive on the inner side of the lower mouth of the furnace body and the adhesive accumulated at the connection between the outer ring and the inner ring of the graphite pressure rod, the degree of adhesion is relatively light, and a simple physical method is used for treatment. The treatment process is: use a stabilizing device to suspend the graphite pressure rod in the air, extend a tapered rod into the graphite pressure rod from top to bottom, squeeze the center of the adhesive accumulation, try not to damage the side wall of the graphite pressure rod, and slowly discharge the adhesive from the bottom of the graphite pressure rod.
[0021] 2) When the adhesive accumulates at the upper end of the lower section of the graphite pressure rod, especially near the outlet of the upper outer ring, the degree of adhesion is relatively serious and needs to be carefully treated at high temperature. The treatment process is: use a stable device to suspend the graphite pressure rod in the air, aim the high-temperature welding gun at the accumulation of adhesive, heat the adhesive, and use the principle of low melting point of the adhesive to melt and discharge the adhesive residue without damaging the experimental equipment.
[0022] Example 1: This iron-containing raw material droplet experimental bonding determination method adopts the following specific steps: The finished balls with the ore structure of 10%A+18%B+33%C+39%D+4.8% slaked lime+0.54% bentonite were screened, and 500g of pellets with a particle size of 10-12.5mm were taken out. Two portions of coke, 80g and 40g respectively, were prepared and put into the graphite crucible in the order of 80g coke, 500g pellets and 40g coke. After flattening, the height was measured in the molten droplet equipment to keep the height of the pellets within the range of 55-58mm. After the pressure difference was tested, the molten droplet experiment was carried out, the heating curve was observed on the computer, and the pressure difference change was recorded. The results are shown in Table 1.
[0023]
[0024] The changes in the center temperature, pressure difference, and weight of the dripping material during the molten drop experiment in Example 1 were recorded and sorted out. The initial center temperature was 0°C, the pressure difference was 0KPa, and the weight of the dripping material was 0g. As the molten drop experiment progressed, when the sequence reached 1419, the center temperature reached 1317°C, and the pressure difference experienced a steep rise and gradually reached the pressure difference peak value P max , which is 9.3KPa. As the experiment progresses, the pressure difference gradually decreases from the peak value. The first pressure difference value after the pressure difference peak decreases is recorded as P h1 At this moment, P1 is 6.8KPa. Then the pressure difference turns back and increases to 7.9KPa again at sequence 1442. After several repeated increases and decreases, the pressure difference gradually increases from 6.0KPa at sequence number 1481, and increases to 15.1KPa after 8.5KPa, and then continues to increase without decreasing. During the entire molten drop test, the weight of the dripping material has been maintained at 0g, which can be judged as the molten drop test adhesion.
[0025] Embodiment 2: This iron-containing raw material droplet experimental bonding determination method adopts the following specific steps: The finished balls with the ore structure of 10%A+18%B+33%C+39%D+4.8% slaked lime+0.54% bentonite were screened, and 500g of pellets with a particle size of 10-12.5mm were taken out. Two portions of coke, 80g and 40g respectively, were prepared and put into the graphite crucible in the order of 80g coke, 500g pellets and 40g coke. After flattening, the height was measured in the molten droplet equipment to keep the height of the pellets within the range of 55-58mm. After the pressure difference was tested, the molten droplet experiment was carried out, the heating curve was observed on the computer, and the pressure difference change was recorded. The results are shown in Table 2.
[0026]
[0027] The changes in the center temperature, pressure difference, and weight of the dripping material during the molten drop experiment in Example 2 were recorded and sorted out. The initial center temperature was 0°C, the pressure difference was 0KPa, and the weight of the dripping material was 0g. As the molten drop experiment progressed, when the sequence reached 1423, the center temperature reached 1321°C, and the pressure difference experienced a steep rise and gradually reached the pressure difference peak value P max , which is 7.3KPa. As the experiment progresses, the pressure difference gradually decreases from the peak value. The first pressure difference value after the pressure difference peak decreases is recorded as P h2 At this moment, P1 is 0.9KPa. Then the pressure difference turns back and increases to 1.3KPa again at sequence 1528. After several repeated increases and decreases, the pressure difference gradually increases from 0.6KPa at sequence number 1555, and increases to 11.8KPa after 3.8KPa, and then continues to increase without decreasing. During the entire molten drop test, the weight of the droplet has been maintained at 0g at the beginning, which can determine that the molten drop test is adhesive.
[0028] Embodiment 3: Effect test after using this graphite pressure rod: The finished balls with the ore structure of 10%A+18%B+33%C+39%D+4.8% slaked lime+0.54% bentonite were sampled, and no less than 10kg of finished balls with a particle size of 10-12.5mm were screened out. Some balls with non-round shapes were removed, and the balls were randomly divided into 6 groups, each with 1kg. Two molten drop experiments were conducted on each group. Among them, the molten drop experiments of the same group used ordinary graphite pressure rods and new graphite pressure rods respectively, and the other experimental conditions remained the same. 80g coke, 500g pellets, and 40g coke were placed in the graphite crucible in order, and the height of the pellets was kept within the range of 55-58mm. After the pressure difference was tested, the molten drop experiment was carried out, mainly recording the type of graphite pressure rod and the weight of the dripping material in the molten drop experiment. The specific results are shown in Table 3.
[0029]
[0030] The weight of dripping material after using ordinary graphite pressure rods and the graphite pressure rod of the present invention in 6 groups of molten drop experiments was compared. Among them, the dripping material weight of the 6 groups of ordinary graphite pressure rods was the highest 209.3g, the lowest 193.5g, and the overall weight was about 202.4g; the dripping material weight of the 6 groups of the present graphite pressure rods was the highest 231.7g, the lowest 216.7g, and the overall weight was about 224.9g. The dripping material weight of the graphite pressure rod using the present invention during the molten drop experiment was 22.5g more than the ordinary graphite pressure rod on average, and the improvement rate was about 11.12%.
[0031] Compared with ordinary graphite pressure rods, the graphite pressure rod has a larger drop weight when the experimental raw materials of the same weight are dripped, which means that the bonding residual rate of the experimental raw materials is lower when the molten drips and flows through the graphite pressure rod. This means that the graphite pressure rod is more excellent in reducing the bonding rate of the molten droplet experiment, which can further reduce the risk of molten droplet bonding, improve experimental accuracy, reduce the cost of experimental consumables, and provide support for operators to judge the blast furnace condition.
Claims
1. A method for determining adhesion of a molten droplet of an iron-containing raw material, characterized in that: When the following situation occurs during the molten drop test, it is determined that the molten drop test has sticking: after the iron-containing raw material begins to melt, the pressure difference rises sharply to a peak, then the pressure difference falls back and then rises again, forming a continuous curve of continuous decline and rise, and finally the pressure difference continues to rise and no longer decreases.
2. The method for determining adhesion of a molten droplet of an iron-containing raw material according to claim 1, characterized in that: When adhesion occurs in the molten drop test, no more dripping occurs or the dripping weight is ≤10g.
3. A method for determining adhesion of a molten droplet of an iron-containing raw material according to claim 1 or 2, characterized in that: The lowest point of each pressure drop is located in the altitude range P h1 or P h2 Inner; said 1KPa<P h1 ≤P max , 0≤P h2 <1KPa.
4. A method for preventing adhesion of iron-containing raw material droplets, characterized in that: The method comprises the following steps: 1) using a conical rod to check whether there is any adhesive residue left in the lower pressure rod from the previous experiment; 2) Check whether the holes at the bottom of the graphite indenter are smooth and not blocked by adhesives, whether the bottom of the indenter is flat and has no bumps, and whether the bottom surface is in stable contact with the test material; 3) Check whether the holes at the bottom of the graphite crucible are smooth and not blocked by adhesives, and whether there are any defects on the inner and outer walls of the graphite crucible.
5. The method for preventing adhesion of iron-containing raw material droplet test according to claim 4, characterized in that: The following graphite pressure rod is used: the diameter difference between the upper outer ring (1) and the lower inner ring (2) of the graphite pressure rod is 1 to 4 cm, and the slope of the bottom end of the upper outer ring (1) is 72.9° to 85.6°.
6. A method for treating the molten droplet bonding of an iron-containing raw material, characterized in that: The process includes the following steps: 1) when the adhesive is accumulated on the upper end of the lower long section of the graphite pressure rod, the bonding part of the graphite pressure rod is subjected to high temperature treatment to melt and discharge the adhesive residue; 2) When the adhesive accumulates at the end of the lower long section of the graphite pressure rod, use a tapered rod to physically remove the adhesive.